2012
DOI: 10.1186/1475-925x-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Iterative integral parameter identification of a respiratory mechanics model

Abstract: BackgroundPatient-specific respiratory mechanics models can support the evaluation of optimal lung protective ventilator settings during ventilation therapy. Clinical application requires that the individual’s model parameter values must be identified with information available at the bedside. Multiple linear regression or gradient-based parameter identification methods are highly sensitive to noise and initial parameter estimates. Thus, they are difficult to apply at the bedside to support therapeutic decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…14,18,20,21 The integral method used to determine the value of the 3 insulin secretion rates U [1][2][3] has similarly been widely employed. 14,23,26,28 The evaluation methods used have seen widespread use, and are widely accepted means of validation.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,20,21 The integral method used to determine the value of the 3 insulin secretion rates U [1][2][3] has similarly been widely employed. 14,23,26,28 The evaluation methods used have seen widespread use, and are widely accepted means of validation.…”
Section: Discussionmentioning
confidence: 99%
“…Airway pressure, flow and volume can be used to identify E rs and R rs using integral-based parameter identification 17 , 26 , 53 in an identifiable problem, 25 where E rs is defined as the average elastance of a single breath. 16 …”
Section: Methodsmentioning
confidence: 99%
“…If t s and t f are known, the airway pressure is a linear combination of volume, flow, time and time squared. This enables the model parameters E, R, a, b, and c to be identified by multiple linear regression [9]. The model can then be formulated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In this study an iterative approach is then used [9], where the identified a, b, and c are used to find t s and t f from the roots of the quadratic function.…”
Section: Methodsmentioning
confidence: 99%